Hubungan Metode Pencucian dan Penyimpanan dengan Angka Kuman Peralatan Makan pada Warung Ayam Geprek di Pontianak Timur - Abdul Syukur; Fitriani Fitriani; Yulia Yulia (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Unhygienic tableware has the potential to become a medium for the transmission of foodborne diseases, especially due to bacterial contamination. According to Ministry of Health Regulation No. 14 of 2021, the bacterial count on dining utensils must not exceed 1.1 CFU/cm². This study aims to analyze the relationship between washing and storage methods of dining utensils and bacterial counts at food handling facilities (FHFs) in the working area of the Saigon Public Health Center (PHC), Pontianak Timur District. The study was conducted as an observational cross-sectional study involving 30 FHP selected through simple random sampling. Data were collected through observation using a checklist and bacterial counts were measured using bacteriological testing with the Total Plate Count (TPC) method. The data were analyzed using the Chi-Square test at a 95% significance level. The results showed that 53% of respondents had good washing practices, while 47% had poor practices; similarly, 50% of respondents had good storage practices, and 50% had poor practices. Bacterial counts on dining utensils were high in 50% of samples and low in 50%. Statistical tests showed no association between washing practices and bacterial counts (p = 0.066), but there was a significant association between storage practices and bacterial counts (p = 0.027). These findings indicate that improper storage practices of dining utensils can increase the risk of microbiological contamination. It is recommended that TPP managers improve the hygiene of dining utensils, and that health departments strengthen routine supervision and education to prevent foodborne illnesses. These findings highlight the importance of systematic interventions in the form of technical training and regular guidance for food managers on standard procedures for hygienic storage of dining utensils. This includes proper arrangement of utensils (e.g., plates upside down), use of closed rust-proof racks, and maintenance of drawers and storage areas to prevent them from becoming breeding grounds for cockroaches, rats, or other disease vectors. Additionally, health departments should strengthen regular monitoring and develop risk-based education programs tailored to on-site resource capacities. With the implementation of these measures, it is hoped that the incidence of foodborne illnesses can be significantly reduced, alongside increased awareness and compliance with hygiene and sanitation principles in food management environments. Keywords: Bacterial Count, Dining Utensils, Washing Methods, Storage Methods.